Konstruksi Kecantikan dalam Novel Midah Si Manis Bergigi Emas dan Cantik Itu Luka - Farida Maesaroh; Dora Hatika Pertiwi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Beauty is a Wound and Midah the Sweet Gold-Toothed and Beauty is a Wound are novels that take women as their main characters. The novel Midah the Sweet Gold-Toothed by Pramoedya Ananta Toer and the novel Beauty is a Wound by Eka Kurniawan are two great works that have received various awards. With the theme of women's struggle, these two novels interpret beauty that is constructed through female characters. This study aims to describe the construction of beauty in the novel Midah the Sweet Gold-Toothed and the novel Beauty is a Wound with a qualitative descriptive approach. The method used in this study is comparative literature, especially to find similarities or differences in the two novels. The theory of beauty construction with the approach of Sigmund Freud's literary psychology is used to obtain the meaning of beauty from the personality of the female character. The results of the analysis of the two novels construct beauty not only about beauty from the inside or outside, but also as a view that beauty can bring misfortune and disaster. The comparison of beauty that emerges from the novel Midah the Sweet Gold-Toothed focuses beauty on one character's personality that is the center of the storyline, namely Midah. The novel Cantik Itu Luka is reconstructed by several female characters such as Dewi Ayu, Cantik, Alamanda, and Aneu with the various stigmas they receive..